Penguatan Kompetensi Karyawan Di Era Digital Marketing Untuk Meningkatkan Produktifitas Usaha Mikro - Tri Mulyani Kartini; Etty Zuliawati Zed; Sinta Sundari Heriyanti; Nasrun Baldah; Suhendra Suhendra (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Human Resources (HR) competency is one of the main factors that must be possessed by MSME business actors. Managing human resources is a skill that must be possessed by business actors. Apart from that, in facing business challenges in the digital era, MSMEs need to adapt to technological developments so as not to be left behind. Therefore, this community service activity aims to provide knowledge about HR competencies in the era of digitalization to business actors in Bekasi Regency, especially North Cikarang. The method used in this community service activity is in the form of counseling and assistance to strengthen employee competency in this era of digitalization, especially the development of digital marketing so that in the future micro businesses have the potential to increase the profitability of their businesses. Human resource management in micro businesses has a specific goal, namely that participants in community service activities are expected to be able to adapt to current developments so that they can maintain the existence of their business and increase their business productivity. Implementation is carried out by providing materials, lectures, discussions/questions and answers and practice with business actors.